Digital Transformation in Halal Certification: Opportunities for SMEs in Indonesia - Syarofi, Muhammad; Syam, Nur (Klabat Journal of Management, 2025)
Many MSMEs in Indonesia continue to face challenges in understanding digital halal certification due to limited access to technology and digital infrastructure. To address this issue, effective technological education and online halal certification training are essential to help MSMEs fully utilize the certification process. This study aims to explore the opportunities and benefits of digital transformation in halal certification for MSMEs. Using a qualitative approach with a case study method, the research focuses on MSMEs in Kraton Village, Kencong, Jember, that have obtained halal certification through a mobile application. Data was collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman method, which includes data reduction, conclusion drawing, and verification. The findings reveal a significant positive impact of digital technology—particularly mobile applications—on the halal certification process for MSMEs. The adoption of digital tools has significantly reduced administrative burdens by simplifying the certification application process, minimizing the need for physical documents, and streamlining bureaucratic procedures. These results indicate that digital technology enhances administrative efficiency, expands market opportunities, and improves access to halal certification. However, this study has limitations, including a narrow sample size and the lack of long-term analysis. Future research should expand the sample, investigate long-term effects, and assess the training and challenges faced by MSMEs in adopting digital halal certification.